N2O Production and Reduction in Chinese Paddy Soils: Linking Microbial Functional Genes with Soil Chemical Properties - Chaobiao Meng; Aoqi Jiang; Yumeng Gao; Xiangyun Yu; Yujie Zhou; Ruiquan Chen; Weijian Shen; Kaijing Yang; Weihan Wang; Dongliang Qi; Cundong Xu; Yonggang Duan (Atmosphere, 2025)
Nitrous oxide (N2O) emissions from paddy soils significantly contribute to global warming; however, the regulatory mechanisms of microbial denitrification remain poorly understood. This study investigated the biotic and abiotic drivers of N2O production and reduction across seven paddy soils spanning China’s major rice-growing regions, using integrated qPCR, incubation experiments, and multivariate analyses. Results demonstrated niche partitioning among denitrifying microorganisms. Pearson correlation analysis demonstrated significant positive correlations between potential N2O production rates and the abundances of denitrification genes (nirS, nirK, and fungal nirK), as well as between N2O reduction rates and nosZ gene abundances (both clade I and II). Key soil chemical properties, including pH, total carbon (TC), and NH4+-N content, showed significant relationships with both potential N2O production rates and reduction rates. Furthermore, random forest analysis identified nirS, fungal nirK, TC, and pH as key predictors of N2O production, while nosZ (clade I and II), TC, and pH governed N2O reduction. Structural equation modeling revealed that nirS-type bacteria predominantly drove N2O production, whereas nosZ II-encoded microorganisms primarily mediated N2O reduction. Moreover, TC exhibited direct positive effects on both processes, while pH indirectly influenced N2O production by regulating nirS abundance and affected reduction via nosZ Ⅱ modulation. These findings provide a mechanistic framework for mitigating agricultural denitrification-derived N2O emissions through a targeted management of soil carbon and pH conditions to optimize complete denitrification.